2011
DOI: 10.1039/c0nr00981d
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of polypropylene-graft-thermally reduced graphite oxide with an improved compatibility with polypropylene-based nanocomposite

Abstract: Polypropylene was successfully covalently grafted onto the surface of thermally reduced graphite oxide (PP-g-TRGO) by taking advantage of the "residual oxygen-containing functional groups" and the "grafting to" method. The PP-g-TRGO obtained showed an improved compatibility, and interfacial interaction, with an isotactic PP (iPP) matrix. The iPP/PP-g-TRGO nanocomposite exhibited a dramatically improved thermal stability compared to that of neat iPP even at low loadings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
60
0
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 51 publications
2
60
0
6
Order By: Relevance
“…However, this improvement seems to be limited by the restacking effect of graphene sheets due to the strong van der Waals interactions between them especially when high amounts of graphene are incorporated into non-polar polyolefin matrices [12]. Therefore, it is imperative to enhance the dispersion of graphene sheets in polyolefin matrices to attain better oxygen barrier performance, which is beneficial to improve the thermo-oxidative stability of graphene-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…However, this improvement seems to be limited by the restacking effect of graphene sheets due to the strong van der Waals interactions between them especially when high amounts of graphene are incorporated into non-polar polyolefin matrices [12]. Therefore, it is imperative to enhance the dispersion of graphene sheets in polyolefin matrices to attain better oxygen barrier performance, which is beneficial to improve the thermo-oxidative stability of graphene-based composites.…”
Section: Introductionmentioning
confidence: 99%
“…The graphene/PP composites with good filler dispersion can also be prepared through a solution mixing manner [39][40][41]. In most studies, PPgMA was used either as the matrix polymer [24,42] or as the compatibilizer for PP/functionalized graphite oxide (fGO) nanocomposites [39,41]. But the effect of the molecular weight of PPgMA was rarely discussed, and it is apparent that a timely study is needed.…”
mentioning
confidence: 99%
“…An alternative to prepare nanoscale dispersed graphene/PP composites via in-situ Ziegler-Natta polymerization in the presence of graphene supported catalyst has been reported [38], but its industrial application is limited by the requirement of sophisticated polymerization techniques. The graphene/PP composites with good filler dispersion can also be prepared through a solution mixing manner [39][40][41]. In most studies, PPgMA was used either as the matrix polymer [24,42] or as the compatibilizer for PP/functionalized graphite oxide (fGO) nanocomposites [39,41].…”
mentioning
confidence: 99%
“…The authors observed that the PP-g-GO acts as multifunctional filler for PP/PPO blends and it enhances the thermal stability and flame-retardant behavior of PP/ PPO blends. Similarly, Ma et al successfully grafted the PP on the surface of TRG covalently and studied the effect of compatibility and thermal stability of isotactic polypropylene (iPP) matrix with the incorporation of PP-g-TRG [108]. It was observed that the PP-g-TRG acts as a heterogeneous nucleation agent and shows a significant improvement in thermal stability of iPP.…”
Section: Thermal and Flame-retardant Behaviors Of Polyolefin/ Graphenmentioning
confidence: 93%